Burned area mapping across the Arctic-boreal zone with Landsat and Sentinel-2 imagery - Stefano Potter; Yili Yang; Arden Burrell; Anna Talucci; Andrew A. Clelland; Sander Veraverbeke; James T. Randerson; Scott J. Goetz; Logan T. Berner; Michelle C. Mack; Xanthe J. Walker; Susan M. Natali; et al. (International Journal of Remote Sensing, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Development and pilot testing of AYA-RISE, a risk information and screening education intervention for adolescents and young adults with cancer risk syndromes - Junne Kamihara; Lauren Fisher; Jaclyn Schienda; Rebecca Vanderwall; Moran Snir; Guy Snir; Emilie Simmons; Andrew Khalaj; Evan Goler; Kayla V. Hamilton; Christopher C. Porter; Bojana Pencheva; et al. (Familial Cancer, 2026)

Bridging the Gap: Enhancing Prostate Cancer Survivorship and Advocacy Among Ethnically Diverse Black Men Through Community Town Halls - Motolani E. Ogunsanya; Ernest Kaninjing; Sara M. DeForge; Daniel J. Morton; Perry Cole; Patrick Beckford; Donald Reese; Thomas Mitchell; Everett Montgomery; Roland Odeleye; Erick Y. Miró-Rivera; Kaitlin Roberts; et al. (Journal of Cancer Education, 2025)
We present findings from town hall meetings held with ethnically diverse Black prostate cancer (CaP) survivors in 2022 and 2023. Four town halls (total participants, N = 265) focused on diagnosis, treatment, psychosocial support, and overall survivorship. Moderated by a long-term CaP survivor, each session featured a panel that included medical providers (urologic oncologists and clinical psychologists), as well as CaP survivors of American, Caribbean, and African origin and their spouses. Surveys captured demographic data, clinical information, CaP-specific details (for survivors only), and perceptions of the town halls. The meetings highlighted three interrelated themesinfluencing decision-making: access to comprehensive information, the strength of support networks, and the availability of culturally competent care. These town halls revealed important educational and support opportunities for ethnically diverse Black men with CaP, promoting informed decision-making throughout the cancer journey and improving quality of life while reducing decisional regret during survivorship.

Designing a blended microbial culture to bioremediate distinct environmental matrices from a complex industrial site contaminated with amino-, nitro-, and chloroaromatic compounds - Isabelle Câmara; Natanna Melo; Line Lomheim; E. Erin Mack; Elizabeth A. Edwards; Jim C. Spain; Osmar Menezes; Savia Gavazza (Environmental Research, 2025)

Fire severity strongly shapes soil enzyme activities in terrestrial ecosystems: insights from a meta-analysis - Hua Chai; Michelle C. Mack; Jie Li; Guiyao Zhou; Jing Wang; Ruiqiang Liu; Zhenggang Du; Hongyang Chen; Yanghui He; Guang Yang; Long Sun; Xuhui Zhou (Plant and Soil, 2025)

A Meta‐Regression of 18 Wildfire Chronosequences Reveals Key Environmental Drivers and Knowledge Gaps in the Boreal Nitrogen Balance - Stefan F. Hupperts; Frank Berninger; Han Y. H. Chen; Nicole Fenton; Mélanie Jean; Kajar Köster; Markku Larjavaara; Michelle C. Mack; Marie‐Charlotte Nilsson; Marjo Palviainen; Anatoly Prokushkin; Jukka Pumpanen; et al. (Global Change Biology, 2025)
Climate change has increased the size and frequency of wildfires across the boreal biome. Severe wildfires in boreal forests have been found to trigger shifts from evergreen to deciduous canopies, which has cascading effects on carbon and nitrogen cycling. Ecosystem productivity and carbon uptake in boreal forests are strongly linked with nitrogen, and Earth system models increasingly depend on our understanding of the nitrogen balance to predict post‐fire carbon uptake. To investigate the post‐fire boreal nitrogen balance, we combined a mass balance approach and literature synthesis to estimate rates of nitrogen accumulation and nitrogen inputs across a network of 18 boreal wildfire chronosequences that varied in both wildfire regime and post‐fire canopy type, comprising 527 forest stands. We found that deciduous‐ or mixed‐dominance boreal forests establishing after severe, stand‐replacing fires had the highest nitrogen accumulation rates (15.7 ± 3.8 kg ha −1 year −1 ), while evergreen‐dominated forests establishing after surface‐ or mixed‐severity fires had the lowest nitrogen accumulation rates (1.4 ± 1.1 kg ha −1 year −1 ). Annual known inputs from nitrogen deposition and biological nitrogen fixation combined, estimated from published data, largely failed to explain the rate of nitrogen accumulation, particularly in deciduous or mixed‐dominance forests establishing after stand‐replacing fires, suggesting that the origins of most nitrogen in these forest types remain poorly understood. As the frequency of severe wildfires increases across the boreal biome and shifts toward deciduous canopies become more common, our study reveals a large knowledge gap in the resulting nitrogen balance that needs to be resolved in order to improve predictions of forest carbon uptake.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Carbon Emissions From Fires in Eastern Siberian Larch Forests - Clement J. F. Delcourt; Brendan M. Rogers; Linar Akhmetzyanov; Brian Izbicki; Rebecca C. Scholten; Tatiana A. Shestakova; Dave van Wees; Michelle C. Mack; Ute Sass‐Klaassen; Sander Veraverbeke (Global Change Biology, 2025)
Siberian boreal forests have experienced increases in fire extent and intensity in recent years, which may threaten their role as carbon (C) sinks. Larch forests ( Larix spp.) cover approximately 2.6 million km 2 across Siberia, yet little is known about the magnitude and drivers of carbon combustion in these ecosystems. To address the paucity of field‐based estimates of fuel load and consumption in Siberian larch forests, we sampled 41 burned plots, one to two years after fire, in Cajander larch ( Larix cajanderi ) forests in the Republic of Sakha (Yakutia), Russia. We estimated pre‐fire carbon stocks and combustion with the objective of identifying the main drivers of carbon emissions. Pre‐fire aboveground (trees and woody debris) and belowground carbon stocks at our study plots were 3.12 ± 1.26 kg C m −2 (mean ± standard deviation) and 3.50 ± 0.93 kg C m −2 . We found that combustion averaged 3.20 ± 0.75 kg C m −2 , of which 78% (2.49 ± 0.56 kg C m −2 ) stemmed from organic soil layers. These results suggest that severe fires in Cajander larch forests can result in combustion rates comparable to those observed in North American boreal forests and exceeding those previously reported for other forest types and burning conditions in Siberia. Carbon combustion was driven by both fire weather conditions and landscape variables, with pre‐fire organic soil depth being the strongest predictor across our plots. Our study highlights the need to better account for Siberian larch forest fires and their impact on the carbon balance, especially given the expected climate‐induced increase in fire extent and severity in this region.

Tundra Vegetation Community Type, Not Microclimate, Controls Asynchrony of Above‐ and Below‐Ground Phenology - Elise C. Gallois; Isla H. Myers‐Smith; Colleen M. Iversen; Verity G. Salmon; Laura L. Turner; Ruby An; Sarah C. Elmendorf; Courtney G. Collins; Madelaine J. R. Anderson; Amanda Young; Lisa Pilkinton; Gesche Blume‐Werry; et al. (Global Change Biology, 2025)
The below‐ground growing season often extends beyond the above‐ground growing season in tundra ecosystems and as the climate warms, shifts in growing seasons are expected. However, we do not yet know to what extent, when and where asynchrony in above‐ and below‐ground phenology occurs and whether variation is driven by local vegetation communities or spatial variation in microclimate. Here, we combined above‐ and below‐ground plant phenology metrics to compare the relative timings and magnitudes of leaf and fine‐root growth and senescence across microclimates and plant communities at five sites across the Arctic and alpine tundra biome. We observed asynchronous growth between above‐ and below‐ground plant tissue, with the below‐ground season extending up to 74% (~56 days) beyond the onset of above‐ground leaf senescence. Plant community type, rather than microclimate, was a key factor controlling the timing, productivity, and growth rates of fine roots, with graminoid roots exhibiting a distinct ‘pulse’ of growth later into the growing season than shrub roots. Our findings indicate the potential of vegetation change to influence below‐ground carbon storage as the climate warms and roots remain active in unfrozen soils for longer. Taken together, our findings of increased root growth in soils that remain thawed later into the growing season, in combination with ongoing tundra vegetation change including increased shrub and graminoid abundance, indicate increased below‐ground productivity and altered carbon cycling in the tundra biome.

Perceptions and knowledge of ecosystem services in urban river systems, Eastern Cape, South Africa - Elizabeth A. Mack; Frank C. Akamagwuna; Chenai Murata; Fenji Materechera-Mitochi; Chika Felicitas Nnadozie; Oghenekaro Nelson Odume (Urban Ecosystems, 2024)
The ecosystem services concept has been studied in rural contexts but not as much in urban landscapes, particularly for aquatic ecosystems in Africa. There is little knowledge of how people perceive ecosystem services (ES) supplied by rivers in urban centres and the factors influencing their perceptions. To fill this gap, the research presented here addresses two objectives: 1) to assess local communities’ perception and knowledge of different types of ecosystem services of an urban river in South Africa, 2) to assess the influence of particular demographic characteristics (age and gender), socio-economic characteristics (education, housing type, income, and years of residence), and prior knowledge of the ecosystem services concept on people’s perception of the ecosystem services provided by the Swartkops River in the Eastern Cape of South Africa. To address these objectives, a team of ten trained field staff collected 181 surveys between May–June 2021 in communities within the river catchment. We used multinomial logit models to analyse the relationships between demographic and socio-economic variables, and people’s perception of ecosystem services. For the majority of the ecosystem services, there was almost an equal split between the perception “sometimes” and “never” that the river provides a particular ecosystem service, and people were less likely to say that the river always provide a particular service. Prior knowledge of the ecosystem services concept, years of residence, age, income and housing type significantly influence people’s perception of ecosystem services. Prior knowledge, was important for the intangible services, whereas years of residence was more important for tangible services with direct use value. Level of formal education was not a significant variable. An important implication of this study is that ecological interventions can be designed through an understanding of factors influencing people’s perceptions of ecosystem services.

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Linking Post-fire Tree Density to Carbon Storage in High-Latitude Cajander Larch (Larix cajanderi) Forests of Far Northeastern Siberia - H. D. Alexander; A. K. Paulson; M. M. Loranty; M. C. Mack; S. M. Natali; H. Pena; S. Davydov; V. Spektor; N. Zimov (Ecosystems, 2024)
With climate warming and drying, fire activity is increasing in Cajander larch ( Larix cajanderi Mayr.) forests underlain by continuous permafrost in northeastern Siberia, and initial post-fire tree demographic processes could unfold to determine long-term forest carbon (C) dynamics through impacts on tree density. Here, we evaluated above- and belowground C pools across 25 even-aged larch stands of varying tree densities that established following a wildfire in ~ 1940 near Cherskiy, Russia. Total C pools increased with increased larch tree density, from ~ 9,000 g C m −2 in low-density stands to ~ 11,000 g C m −2 in high and very high-density stands, with increases most pronounced at tree densities < 1 stem m −2 and driven by increased above- and belowground (that is, coarse roots) and live and dead (that is, woody debris and snags) larch biomass. Total understory vegetation and non-larch coarse root C pools declined with increased tree density due to decreased shrub C pools, but these pools were relatively small compared to larch biomass. Fine root, soil organic matter (OM), and near surface (0–30 cm) mineral soil (MS) C pools varied little with tree density, although soil C pools held most (18–28% in OM and 44–51% in MS) C stored in these stands. Thus, if changing fire regimes promote denser stands, C storage will likely increase, but whether this increase offsets C lost during fires remains unknown. Our findings highlight how post-fire tree demographic processes impact C pool distribution and stability in larch forests of Siberian permafrost regions.

Identification of neural-relevant toxcast high-throughput assay intended gene targets: Applicability to neurotoxicity and neurotoxicant putative molecular initiating events - Cina M. Mack; Alethea Tsui-Bowen; Alicia R. Smith; Karl F. Jensen; Prasada Rao S. Kodavanti; Virginia C. Moser; William R. Mundy; Timothy J. Shafer; David W. Herr (NeuroToxicology, 2024)

How specific combinations of epoch length, non-wear time and cut-points influence physical activity - Alexander Burchartz; Simon Kolb; Leon Klos; Steffen C. E. Schmidt; Birte von Haaren-Mack; Claudia Niessner; Alexander Woll (German Journal of Exercise and Sport Research, 2024)
This study assesses three factors that influence the quantification of children’s and adolescents’ physical activity (PA) using accelerometers: selection of (1) non-wear algorithm, (2) epoch length and (3) cut-points. A total of 1525 participants from MoMo wave 3 (2018–2022), aged 6–17 years, wore GT3X accelerometers (ActiGraph, LLC, Pensacola, FL, USA) during waking hours. Acceleration counts were reintegrated into lengths of 1, 5, 15, 30, and 60 s epochs. Two non-wear time algorithms and two sets of cut-points were applied to each epoch length. Differences were found in both the comparison of the non-wear time algorithms and the comparison of the cut-points when the different epoch lengths were considered. This may result in large differences in estimated sedentary behavior and PA values. We propose to pool the data by merging and combining multiple accelerometer datasets from different studies and evaluate them in a harmonized way in the future. In addition to the need for future validation studies using short epoch lengths for young children, we also propose to conduct meta-analyses. This allows the use of data from multiple studies to validate cut-points and to propose a consensual set of cut-points that can be used in different settings and projects. The high discrepancy between results when comparing different epoch lengths has to be considered when interpreting accelerometer data and is regarded a confounding variable when comparing levels of PA between studies.

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Journals must expand access to peer review data - Olivia M. Smith; Kayla L. Davis; Robin Waterman; Riley B. Pizza; Caitlin Mack; Emily E. Conway; Kara C. Dobson; Brianna Foster; Ani E. Hristova; Julie C. Jarvey; Nan Nourn; Courtney L. Davis (Trends in Ecology & Evolution, 2024)

Shifts in Ecological Legacies Support Hysteresis of Stand Type Conversions in Boreal Forests - X. J. Walker; K. Okano; L. T. Berner; R. Massey; S. J. Goetz; J. F. Johnstone; M. C. Mack (Ecosystems, 2023)

Post-fire Recovery of Soil Organic Layer Carbon in Canadian Boreal Forests - Kristen E. Bill; Catherine M. Dieleman; Jennifer L. Baltzer; Geneviève É. Degré-Timmons; Michelle C. Mack; Nicola J. Day; Steve G. Cumming; Xanthe J. Walker; Merritt R. Turetsky (Ecosystems, 2023)

Decadal impacts of wildfire fuel reduction treatments on ecosystem characteristics and fire behavior in alaskan boreal forests - Melissa A. Boyd; Xanthe J. Walker; Jennifer Barnes; Gerardo Celis; Scott J. Goetz; Jill F. Johnstone; Nicholas T. Link; April M. Melvin; Lisa Saperstein; Edward A.G. Schuur; Michelle C. Mack (Forest Ecology and Management, 2023)

Cryptic carnivores: Intercontinental sampling reveals extensive novel diversity in a genus of freshwater annelids - Joseph M. Mack; Mårten Klinth; Svante Martinsson; Robert Lu; Hannah Stormer; Patrick Hanington; Heather C. Proctor; Christer Erséus; Alexandra E. Bely (Molecular Phylogenetics and Evolution, 2023)

Electrical Stimulation of the Auricular Branch Vagus Nerve Using Random and Alternating Frequencies Triggers a Rapid Onset and Pronounced Antihyperalgesia via Peripheral Annexin A1-Formyl Peptide Receptor 2/ALX Pathway in a Mouse Model of Persistent Inflammatory Pain - Daiana C. Salm; Verônica V. Horewicz; Fernanda Tanaka; Júlia K. Ferreira; Bruna H. de Oliveira; Julia Maria Batista Maio; Nathalia N. Donatello; Daniela D. Ludtke; Leidiane Mazzardo-Martins; Aline R. Dutra; Josiel M. Mack; Deborah de C. H. Kunzler; et al. (Molecular Neurobiology, 2023)

Host identity affects the response of mycorrhizal fungal communities to high severity fires in Alaskan boreal forests - M. Rae DeVan; Jill F. Johnstone; Michelle C. Mack; Teresa N. Hollingsworth; D. Lee Taylor (Fungal Ecology, 2023)

Material Legacies and Environmental Constraints Underlie Fire Resilience of a Dominant Boreal Forest Type - Nicola J. Day; Jill F. Johnstone; Kirsten A. Reid; Steven G. Cumming; Michelle C. Mack; Merritt R. Turetsky; Xanthe J. Walker; Jennifer L. Baltzer (Ecosystems, 2023)
Resilience of plant communities to disturbance is supported by multiple mechanisms, including ecological legacies affecting propagule availability, species’ environmental tolerances, and biotic interactions. Understanding the relative importance of these mechanisms for plant community resilience supports predictions of where and how resilience will be altered with disturbance. We tested mechanisms underlying resilience of forests dominated by black spruce ( Picea mariana ) to fire disturbance across a heterogeneous forest landscape in the Northwest Territories, Canada. We combined surveys of naturally regenerating seedlings at 219 burned plots with experimental manipulations of ecological legacies via seed addition of four tree species and vertebrate exclosures to limit granivory and herbivory at 30 plots varying in moisture and fire severity. Black spruce recovery was greatest where it dominated pre-fire, at wet sites with deep residual soil organic layers, and fire conditions of low soil or canopy combustion and longer return intervals. Experimental addition of seed indicated all species were seed-limited, emphasizing the importance of propagule legacies. Black spruce and birch ( Betula papyrifera ) recruitment were enhanced with vertebrate exclusion. Our combination of observational and experimental studies demonstrates black spruce is vulnerable to effects of increased fire activity that erode ecological legacies. Moreover, black spruce relies on wet areas with deep soil organic layers where other species are less competitive. However, other species can colonize these areas if enough seed is available or soil moisture is altered by climate change. Testing mechanisms underlying species’ resilience to disturbance aids predictions of where vegetation will transform with effects of climate change.

Multilevel Associations with Cancer Screening Among Women in Rural, Segregated Communities Within the Northeastern USA: a Mixed-Methods Study - Jennifer L. Moss; Kelsey Leach; Kelsey C. Stoltzfus; Marni Granzow; Paul L. Reiter; Tracy Onega; Lisa M. Klesges; Mack T. Ruffin (Journal of Cancer Education, 2022)

Impact of weekdays versus weekend days on accelerometer measured physical behavior among children and adolescents: results from the MoMo study - Alexander Burchartz; Doris Oriwol; Simon Kolb; Steffen C. E. Schmidt; Birte von Haaren-Mack; Claudia Niessner; Alexander Woll (German Journal of Exercise and Sport Research, 2022)
Structured activities, in which children participate for example at school, are consistent and limited in scope. After-school or weekend activities, by contrast, involve a wider range of behaviors. Studies have shown that physical activity (PA), as measured by accelerometers, is lower on weekends compared to weekdays or school days, whereas PA does not differ between weekdays. In the present study, we examined accelerometer data of children and adolescents living in Germany for the different weekdays and weekend days. The current analysis used cross-sectional data of participants ( n = 2743) aged 6–17 years collected between 2014 and 2017. The final valid sample consisted of 2278 children and adolescents divided into three age groups (6–10 years, n = 713; 11–13 years, n = 706; 14–17 years, n = 859) and two gender groups (1072 boys, 1206 girls). Physical behavior, including sedentary behavior, as well as light, moderate, vigorous PA, and wear time were analyzed. Absolute and percentage intensity distributions were evaluated daily. The average wear time was 807 min daily from Monday–Thursday with significant deviations from the mean on Friday (+38 min), Saturday (−76 min), and Sunday (−141 min). Absolute moderate to vigorous PA times were lower on weekends than during the week. However, the percentage intensity distribution remained constant over all days. Girls were less physically active and more sedentary than boys (F 1,2272 = 38.3; p < 0.01) and adolescents were significantly less active than younger children (F 2,2272 = 138.6; p < 0.01). Waking times increased with age (F 2,2272 = 138.6; p < 0.01). Shorter awake periods limit possible active times on weekends, resulting in lower PA and sedentary behavior compared to weekdays. The percentage distributions of the different physical behavior intensity categories are similar over all weekdays and weekend days. We could not find a justification for specific weekend interventions. Instead, interventions should generally try to shift activity away from sedentary behavior towards a more active lifestyle.

Decreased growth of wild soil microbes after 15 years of transplant‐induced warming in a montane meadow - Alicia M. Purcell; Michaela Hayer; Benjamin J. Koch; Rebecca L. Mau; Steven J. Blazewicz; Paul Dijkstra; Michelle C. Mack; Jane C. Marks; Ember M. Morrissey; Jennifer Pett‐Ridge; Rachel L. Rubin; Egbert Schwartz; et al. (Global Change Biology, 2022)
The carbon stored in soil exceeds that of plant biomass and atmospheric carbon and its stability can impact global climate. Growth of decomposer microorganisms mediates both the accrual and loss of soil carbon. Growth is sensitive to temperature and given the vast biological diversity of soil microorganisms, the response of decomposer growth rates to warming may be strongly idiosyncratic, varying among taxa, making ecosystem predictions difficult. Here, we show that 15 years of warming by transplanting plant–soil mesocosms down in elevation, strongly reduced the growth rates of soil microorganisms, measured in the field using undisturbed soil. The magnitude of the response to warming varied among microbial taxa. However, the direction of the response—reduced growth—was universal and warming explained twofold more variation than did the sum of taxonomic identity and its interaction with warming. For this ecosystem, most of the growth responses to warming could be explained without taxon‐specific information, suggesting that in some cases microbial responses measured in aggregate may be adequate for climate modeling. Long‐term experimental warming also reduced soil carbon content, likely a consequence of a warming‐induced increase in decomposition, as warming‐induced changes in plant productivity were negligible. The loss of soil carbon and decreased microbial biomass with warming may explain the reduced growth of the microbial community, more than the direct effects of temperature on growth. These findings show that direct and indirect effects of long‐term warming can reduce growth rates of soil microbes, which may have important feedbacks to global warming.

The relationship of C and N stable isotopes to high-latitude moss-associated N2 fixation - Julia E. M. Stuart; Hannah Holland-Moritz; Mélanie Jean; Samantha N. Miller; José Miguel Ponciano; Stuart F. McDaniel; Michelle C. Mack (Oecologia, 2021)

Deep roots of Carex aquatilis have greater ammonium uptake capacity than shallow roots in peatlands following permafrost thaw - Lucas J. Albano; Merritt R. Turetsky; Michelle C. Mack; Evan S. Kane (Plant and Soil, 2021)

Host Identity as a Driver of Moss-Associated N2 Fixation Rates in Alaska - Julia E. M. Stuart; Hannah Holland-Moritz; Lily R. Lewis; Mélanie Jean; Samantha N. Miller; Stuart F. McDaniel; Noah Fierer; José Miguel Ponciano; Michelle C. Mack (Ecosystems, 2021)

Atmospheric stilling and warming air temperatures drive long‐term changes in lake stratification in a large oligotrophic lake - Jonathan T. Stetler; Scott Girdner; Jeremy Mack; Luke A. Winslow; Taylor H. Leach; Kevin C. Rose (Limnology and Oceanography, 2021)
Lake surface temperatures are warming in many regions and have the potential to alter seasonal thermal stratification. However, the effects of climate change on thermal stratification can be difficult to characterize because trends in thermal stratification can be regulated by changes in multiple climate variables and other characteristics, such as water clarity. Here, we use long‐term (1993–2017) data from near‐pristine Crater Lake (Oregon) to understand long‐term changes in the depth and strength of summer stratification, measured by the center of buoyancy and Schmidt Stability, respectively. The depth of stratification has shoaled significantly (2.4 m decade −1 ), while stratification strength exhibited no long‐term trend. Empirical observations and modeling scenarios demonstrate that atmospheric stilling at Crater Lake is associated with the 25‐year shoaling trend as spring wind speeds declined over the observation period. While summer lake surface water and air temperatures warmed during the study period, spring air temperatures were variable and correlated with summer Schmidt Stability. Our results indicate that warmer spring air temperature resulted in earlier onset of stratification and stronger summer stratification. The observed shoaling of stratification depth at Crater Lake may have important ecological consequences, especially for non‐motile primary producers who can become constrained within a thinner epilimnion and exposed to higher solar radiation and reduced upwelling of nutrients. Driven by climate changes, many large lakes may be experiencing similar trends in seasonal stratification.

Wildfire combustion and carbon stocks in the southern Canadian boreal forest: Implications for a warming world - Catherine M. Dieleman; Brendan M. Rogers; Stefano Potter; Sander Veraverbeke; Jill F. Johnstone; Jocelyne Laflamme; Kylen Solvik; Xanthe J. Walker; Michelle C. Mack; Merritt R. Turetsky (Global Change Biology, 2020)
Boreal wildfires are increasing in intensity, extent, and frequency, potentially intensifying carbon emissions and transitioning the region from a globally significant carbon sink to a source. The productive southern boreal forests of central Canada already experience relatively high frequencies of fire, and as such may serve as an analog of future carbon dynamics for more northern forests. Fire–carbon dynamics in southern boreal systems are relatively understudied, with limited investigation into the drivers of pre‐fire carbon stocks or subsequent combustion. As part of NASA's Arctic‐Boreal Vulnerability Experiment, we sampled 79 stands (47 burned, 32 unburned) throughout central Saskatchewan to characterize above‐ and belowground carbon stocks and combustion rates in relation to historical land use, vegetation characteristics, and geophysical attributes. We found southern boreal forests emitted an average of 3.3 ± 1.1 kg C/m 2 from field sites. The emissions from southern boreal stands varied as a function of stand age, fire weather conditions, ecozone, and soil moisture class. Sites affected by historical timber harvesting had greater combustion rates due to faster carbon stock recovery rates than sites recovering from wildfire events, indicating that different boreal forest land use practices can generate divergent carbon legacy effects. We estimate the 2015 fire season in Saskatchewan emitted a total of 36.3 ± 15.0 Tg C, emphasizing the importance of southern boreal fires for regional carbon budgets. Using the southern boreal as an analog, the northern boreal may undergo fundamental shifts in forest structure and carbon dynamics, becoming dominated by stands 2 less than current mature northern boreal stands. Our latitudinal approach reinforces previous studies showing that northern boreal stands are at a high risk of holding less carbon under changing disturbance conditions.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Climate change decreases the cooling effect from postfire albedo in boreal North America - Stefano Potter; Kylen Solvik; Angela Erb; Scott J. Goetz; Jill F. Johnstone; Michelle C. Mack; James T. Randerson; Miguel O. Román; Crystal L. Schaaf; Merritt R. Turetsky; Sander Veraverbeke; Xanthe J. Walker; et al. (Global Change Biology, 2020)
Fire is a primary disturbance in boreal forests and generates both positive and negative climate forcings. The influence of fire on surface albedo is a predominantly negative forcing in boreal forests, and one of the strongest overall, due to increased snow exposure in the winter and spring months. Albedo forcings are spatially and temporally heterogeneous and depend on a variety of factors related to soils, topography, climate, land cover/vegetation type, successional dynamics, time since fire, season, and fire severity. However, how these variables interact to influence albedo is not well understood, and quantifying these relationships and predicting postfire albedo becomes increasingly important as the climate changes and management frameworks evolve to consider climate impacts. Here we developed a MODIS‐derived ‘blue sky’ albedo product and a novel machine learning modeling framework to predict fire‐driven changes in albedo under historical and future climate scenarios across boreal North America. Converted to radiative forcing (RF), we estimated that fires generate an annual mean cooling of −1.77 ± 1.35 W/m 2 from albedo under historical climate conditions (1971–2000) integrated over 70 years postfire. Increasing postfire albedo along a south–north climatic gradient was offset by a nearly opposite gradient in solar insolation, such that large‐scale spatial patterns in RF were minimal. Our models suggest that climate change will lead to decreases in mean annual postfire albedo, and hence a decreasing strength of the negative RF, a trend dominated by decreased snow cover in spring months. Considering the range of future climate scenarios and model uncertainties, we estimate that for fires burning in the current era (2016) the cooling effect from long‐term postfire albedo will be reduced by 15%–28% due to climate change.

Broadleaf Litter Controls Feather Moss Growth in Black Spruce and Birch Forests of Interior Alaska - Mélanie Jean; April M. Melvin; Michelle C. Mack; Jill F. Johnstone (Ecosystems, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Inherited alterations of TGF beta signaling components in Appalachian cervical cancers - Thomas J. Knobloch; Juan Peng; Erinn M. Hade; David E. Cohn; Mack T. Ruffin; Michael A. Schiano; Byron C. Calhoun; William C. McBee; Jamie L. Lesnock; Holly H. Gallion; Jondavid Pollock; Bo Lu; et al. (Cancer Causes & Control, 2019)

Improving Hydric Soil Identification in Areas Containing Problematic Red Parent Materials: a Nationwide Collaborative Mapping Approach - Sara C. Mack; Jacob F. Berkowitz; Martin C. Rabenhorst (Wetlands, 2019)

Wildfire severity reduces richness and alters composition of soil fungal communities in boreal forests of western Canada - Nicola J. Day; Kari E. Dunfield; Jill F. Johnstone; Michelle C. Mack; Merritt R. Turetsky; Xanthe J. Walker; Alison L. White; Jennifer L. Baltzer (Global Change Biology, 2019)
Wildfire is the dominant disturbance in boreal forests and fire activity is increasing in these regions. Soil fungal communities are important for plant growth and nutrient cycling postfire but there is little understanding of how fires impact fungal communities across landscapes, fire severity gradients, and stand types in boreal forests. Understanding relationships between fungal community composition, particularly mycorrhizas, and understory plant composition is therefore important in predicting how future fire regimes may affect vegetation. We used an extreme wildfire event in boreal forests of Canada's Northwest Territories to test drivers of fungal communities and assess relationships with plant communities. We sampled soils from 39 plots 1 year after fire and 8 unburned plots. High‐throughput sequencing (MiSeq, ITS) revealed 2,034 fungal operational taxonomic units. We found soil pH and fire severity (proportion soil organic layer combusted), and interactions between these drivers were important for fungal community structure (composition, richness, diversity, functional groups). Where fire severity was low, samples with low pH had higher total fungal, mycorrhizal, and saprotroph richness compared to where severity was high. Increased fire severity caused declines in richness of total fungi, mycorrhizas, and saprotrophs, and declines in diversity of total fungi and mycorrhizas. The importance of stand age (a surrogate for fire return interval) for fungal composition suggests we could detect long‐term successional patterns even after fire. Mycorrhizal and plant community composition, richness, and diversity were weakly but significantly correlated. These weak relationships and the distribution of fungi across plots suggest that the underlying driver of fungal community structure is pH, which is modified by fire severity. This study shows the importance of edaphic factors in determining fungal community structure at large scales, but suggests these patterns are mediated by interactions between fire and forest stand composition.

Decomposition of Senesced Leaf Litter is Faster in Tall Compared to Low Birch Shrub Tundra - Casper T. Christiansen; Michelle C. Mack; Jennie DeMarco; Paul Grogan (Ecosystems, 2018)

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

Nutrient limitation of plant productivity in scrubby flatwoods: does fire shift nitrogen versus phosphorus limitation? - Jennifer L. Schafer; Michelle C. Mack (Plant Ecology, 2018)

Cross‐scale controls on carbon emissions from boreal forest megafires - Xanthe J. Walker; Brendan M. Rogers; Jennifer L. Baltzer; Steven G. Cumming; Nicola J. Day; Scott J. Goetz; Jill F. Johnstone; Edward A. G. Schuur; Merritt R. Turetsky; Michelle C. Mack (Global Change Biology, 2018)
Climate warming and drying is associated with increased wildfire disturbance and the emergence of megafires in North American boreal forests. Changes to the fire regime are expected to strongly increase combustion emissions of carbon (C) which could alter regional C balance and positively feedback to climate warming. In order to accurately estimate C emissions and thereby better predict future climate feedbacks, there is a need to understand the major sources of heterogeneity that impact C emissions at different scales. Here, we examined 211 field plots in boreal forests dominated by black spruce ( Picea mariana ) or jack pine ( Pinus banksiana ) of the Northwest Territories ( NWT ), Canada after an unprecedentedly large area burned in 2014. We assessed both aboveground and soil organic layer ( SOL ) combustion, with the goal of determining the major drivers in total C emissions, as well as to develop a high spatial resolution model to scale emissions in a relatively understudied region of the boreal forest. On average, 3.35 kg C m −2 was combusted and almost 90% of this was from SOL combustion. Our results indicate that black spruce stands located at landscape positions with intermediate drainage contribute the most to C emissions. Indices associated with fire weather and date of burn did not impact emissions, which we attribute to the extreme fire weather over a short period of time. Using these results, we estimated a total of 94.3 Tg C emitted from 2.85 Mha of burned area across the entire 2014 NWT fire complex, which offsets almost 50% of mean annual net ecosystem production in terrestrial ecosystems of Canada. Our study also highlights the need for fine‐scale estimates of burned area that represent small water bodies and regionally specific calibrations of combustion that account for spatial heterogeneity in order to accurately model emissions at the continental scale.

Spatial and temporal variation in moss-associated dinitrogen fixation in coniferous- and deciduous-dominated Alaskan boreal forests - Mélanie Jean; Michelle C. Mack; Jill F. Johnstone (Plant Ecology, 2018)

Novel bacterial lineages associated with boreal moss species - Hannah Holland‐Moritz; Julia Stuart; Lily R. Lewis; Samantha Miller; Michelle C. Mack; Stuart F. McDaniel; Noah Fierer (Environmental Microbiology, 2018)
Summary Mosses are critical components of boreal ecosystems where they typically account for a large proportion of net primary productivity and harbour diverse bacterial communities that can be the major source of biologically‐fixed nitrogen in these ecosystems. Despite their ecological importance, we have limited understanding of how microbial communities vary across boreal moss species and the extent to which local site conditions may influence the composition of these bacterial communities. We used marker gene sequencing to analyze bacterial communities associated with seven boreal moss species collected near Fairbanks, AK, USA. We found that host identity was more important than site in determining bacterial community composition and that mosses harbour diverse lineages of potential N 2 ‐fixers as well as an abundance of novel taxa assigned to understudied bacterial phyla (including candidate phylum WPS‐2). We performed shotgun metagenomic sequencing to assemble genomes from the WPS‐2 candidate phylum and found that these moss‐associated bacteria are likely anoxygenic phototrophs capable of carbon fixation via RuBisCo with an ability to utilize byproducts of photorespiration from hosts via a glyoxylate shunt. These results give new insights into the metabolic capabilities of understudied bacterial lineages that associate with mosses and the importance of plant hosts in shaping their microbiomes.

Rooting depth varies differentially in trees and grasses as a function of mean annual rainfall in an African savanna - Ricardo M. Holdo; Jesse B. Nippert; Michelle C. Mack (Oecologia, 2018)

Predicting Ecosystem Resilience to Fire from Tree Ring Analysis in Black Spruce Forests - Xanthe J. Walker; Michelle C. Mack; Jill F. Johnstone (Ecosystems, 2017)

Internet Usage Trends in Thoracic Surgery Patients and Their Caregivers - Alisha D. Lussiez; Stephanie Burdick; Sindhura Kodali; Gustavo Rubio; Jacob A. Mack; Jules Lin; Andrew C. Chang; Rishindra M. Reddy (Journal of Cancer Education, 2017)

Losing Legacies, Ecological Release, and Transient Responses: Key Challenges for the Future of Northern Ecosystem Science - Merritt R. Turetsky; Jennifer L. Baltzer; Jill F. Johnstone; Michelle C. Mack; Kevin McCann; Edward A. G. Schuur (Ecosystems, 2017)

Nitrogen availability increases in a tundra ecosystem during five years of experimental permafrost thaw - Verity G. Salmon; Patrick Soucy; Marguerite Mauritz; Gerardo Celis; Susan M. Natali; Michelle C. Mack; Edward A. G. Schuur (Global Change Biology, 2016)
Perennially frozen soil in high latitude ecosystems (permafrost) currently stores 1330–1580 Pg of carbon (C). As these ecosystems warm, the thaw and decomposition of permafrost is expected to release large amounts of C to the atmosphere. Fortunately, losses from the permafrost C pool will be partially offset by increased plant productivity. The degree to which plants are able to sequester C, however, will be determined by changing nitrogen (N) availability in these thawing soil profiles. N availability currently limits plant productivity in tundra ecosystems but plant access to N is expected improve as decomposition increases in speed and extends to deeper soil horizons. To evaluate the relationship between permafrost thaw and N availability, we monitored N cycling during 5 years of experimentally induced permafrost thaw at the Carbon in Permafrost Experimental Heating Research (Ci PEHR ) project. Inorganic N availability increased significantly in response to deeper thaw and greater soil moisture induced by Soil warming. This treatment also prompted a 23% increase in aboveground biomass and a 49% increase in foliar N pools. The sedge Eriophorum vaginatum responded most strongly to warming: this species explained 91% of the change in aboveground biomass during the 5 year period. Air warming had little impact when applied alone, but when applied in combination with Soil warming, growing season soil inorganic N availability was significantly reduced. These results demonstrate that there is a strong positive relationship between the depth of permafrost thaw and N availability in tundra ecosystems but that this relationship can be diminished by interactions between increased thaw, warmer air temperatures, and higher levels of soil moisture. Within 5 years of permafrost thaw, plants actively incorporate newly available N into biomass but C storage in live vascular plant biomass is unlikely to be greater than losses from deep soil C pools.

A Framework to Assess Biogeochemical Response to Ecosystem Disturbance Using Nutrient Partitioning Ratios - J. Marty Kranabetter; Kendra K. McLauchlan; Sara K. Enders; Jennifer M. Fraterrigo; Philip E. Higuera; Jesse L. Morris; Edward B. Rastetter; Rebecca Barnes; Brian Buma; Daniel G. Gavin; Laci M. Gerhart; Lindsey Gillson; et al. (Ecosystems, 2016)

Natural history collections as windows on evolutionary processes - Michael W. Holmes; Talisin T. Hammond; Guinevere O. U. Wogan; Rachel E. Walsh; Katie LaBarbera; Elizabeth A. Wommack; Felipe M. Martins; Jeremy C. Crawford; Katya L. Mack; Luke M. Bloch; Michael W. Nachman (Molecular Ecology, 2016)
Natural history collections provide an immense record of biodiversity on Earth. These repositories have traditionally been used to address fundamental questions in biogeography, systematics and conservation. However, they also hold the potential for studying evolution directly. While some of the best direct observations of evolution have come from long‐term field studies or from experimental studies in the laboratory, natural history collections are providing new insights into evolutionary change in natural populations. By comparing phenotypic and genotypic changes in populations through time, natural history collections provide a window into evolutionary processes. Recent studies utilizing this approach have revealed some dramatic instances of phenotypic change over short timescales in response to presumably strong selective pressures. In some instances, evolutionary change can be paired with environmental change, providing a context for potential selective forces. Moreover, in a few cases, the genetic basis of phenotypic change is well understood, allowing for insight into adaptive change at multiple levels. These kinds of studies open the door to a wide range of previously intractable questions by enabling the study of evolution through time, analogous to experimental studies in the laboratory, but amenable to a diversity of species over longer timescales in natural populations.

A Canopy Shift in Interior Alaskan Boreal Forests: Consequences for Above- and Belowground Carbon and Nitrogen Pools during Post-fire Succession - Heather D. Alexander; Michelle C. Mack (Ecosystems, 2016)

Differences in Ecosystem Carbon Distribution and Nutrient Cycling Linked to Forest Tree Species Composition in a Mid-Successional Boreal Forest - April M. Melvin; Michelle C. Mack; Jill F. Johnstone; A. David McGuire; Helene Genet; Edward A. G. Schuur (Ecosystems, 2015)

Stable carbon isotope analysis reveals widespread drought stress in boreal black spruce forests - Xanthe J. Walker; Michelle C. Mack; Jill F. Johnstone (Global Change Biology, 2015)
Unprecedented rates of climate warming over the past century have resulted in increased forest stress and mortality worldwide. Decreased tree growth in association with increasing temperatures is generally accepted as a signal of temperature‐induced drought stress. However, variations in tree growth alone do not reveal the physiological mechanisms behind recent changes in tree growth. Examining stable carbon isotope composition of tree rings in addition to tree growth can provide a secondary line of evidence for physiological drought stress. In this study, we examined patterns of black spruce growth and carbon isotopic composition in tree rings in response to climate warming and drying in the boreal forest of interior Alaska. We examined trees at three nested scales: landscape, toposequence, and a subsample of trees within the toposequence. At each scale, we studied the potential effects of differences in microclimate and moisture availability by sampling on northern and southern aspects. We found that black spruce radial growth responded negatively to monthly metrics of temperature at all examined scales, and we examined ∆ 13 C responses on a subsample of trees as representative of the wider region. The negative ∆ 13 C responses to temperature reveal that black spruce trees are experiencing moisture stress on both northern and southern aspects. Contrary to our expectations, ∆ 13 C from trees on the northern aspect exhibited the strongest drought signal. Our results highlight the prominence of drought stress in the boreal forest of interior Alaska. We conclude that if temperatures continue to warm, we can expect drought‐induced productivity declines across large regions of the boreal forest, even for trees located in cool and moist landscape positions.

Spatially explicit estimation of aboveground boreal forest biomass in the Yukon River Basin, Alaska - Lei Ji; Bruce K. Wylie; Dana R. N. Brown; Birgit Peterson; Heather D. Alexander; Michelle C. Mack; Jennifer Rover; Mark P. Waldrop; Jack W. McFarland; Xuexia Chen; Neal J. Pastick (International Journal of Remote Sensing, 2015)

Effects of arctic shrub expansion on biophysical vs. biogeochemical drivers of litter decomposition - Jennie DeMarco; Michelle C. Mack; M. Syndonia Bret-Harte (Ecology, 2014)
Climate warming in arctic tundra may shift dominant vegetation from graminoids to deciduous shrubs, whose functional traits could, in turn, alter biotic and abiotic controls over biogeochemical cycling of carbon (C) and nitrogen (N). We investigated whether shrub‐induced changes in microclimate have stronger effects on litter decomposition and nutrient release than changes in litter quality and quantity. In arctic tundra near Toolik Lake, Alaska, USA, we incubated a common substrate in a snow‐addition experiment to test whether snow accumulation around arctic deciduous shrubs altered the environment enough to increase litter decomposition rates. We compared the influence of litter quality on the rate of litter and N loss by decomposing litter from four different plant functional types in a common site. We used aboveground net primary production values and estimated decay constant ( k ) values from our decomposition experiments to calculate community‐weighted mass loss for each site. Snow addition had no effect on decomposition of the common substrate, and the site with the highest abundance of shrubs had the lowest decomposition rates. Species varied in their decomposition rates, with species from the same functional type not always following similar patterns. Community‐weighted mass loss was 1.5 times greater in the high shrub site, and only slightly decreased when adjusted for soil environment, suggesting that litter quality and quantity are the primary drivers of community decomposition. Our findings suggest that on a short time scale, the changes in soil environment associated with snow trapping by shrubs are unlikely to influence litter nutrient turnover enough to drive positive snow–shrub feedbacks. The mechanisms driving shrub expansion are more likely to do with shrub–litter feedbacks, where the higher growth rates and N uptake by shrubs allows them to produce more leaves, resulting in a larger litter N pool and faster internal cycling of nutrients.

Pyrogeography, historical ecology, and the human dimensions of fire regimes - Christopher I. Roos; David M. J. S. Bowman; Jennifer K. Balch; Paulo Artaxo; William J. Bond; Mark Cochrane; Carla M. D'Antonio; Ruth DeFries; Michelle Mack; Fay H. Johnston; Meg A. Krawchuk; Christian A. Kull; et al. (Journal of Biogeography, 2014)
In our 2011 synthesis (Bowman et al ., Journal of Biogeography , 2011, 38 , 2223–2236), we argued for a holistic approach to human issues in fire science that we term ‘pyrogeography’. Coughlan & Petty ( Journal of Biogeography , 2013, 40 , 1010–1012) critiqued our paper on the grounds that our ‘pyric phase’ model was built on outdated views of cultural development, claiming we developed it to be the unifying explanatory framework for all human–fire sciences. Rather, they suggest that ‘historical ecology’ could provide such a framework. We used the ‘pyric transition’ for multiple purposes but did not offer it as an exclusive explanatory framework for pyrogeography. Although ‘historical ecology’ is one of many useful approaches to studying human–fire relationships, scholars should also look to political and evolutionary ecology, ecosystems and complexity theories, as well as empirical generalizations to build an interdisciplinary fire science that incorporates human, ecological and biophysical dimensions of fire regimes.

Tobacco smoking, NBS1 polymorphisms, and survival in lung and upper aerodigestive tract cancers with semi-Bayes adjustment for hazard ratio variation - Tingting Yang; Po-Yin Chang; Sungshim Lani Park; Delara Bastani; Shen-Chih Chang; Hal Morgenstern; Donald P. Tashkin; Jenny T. Mao; Jeanette C. Papp; Jian-Yu Rao; Wendy Cozen; Thomas M. Mack; et al. (Cancer Causes & Control, 2014)

Shade tolerance of temperate Asian bamboos: a harbinger of their naturalization in Pacific Northwest coniferous forests? - Melissa C. Smith; Richard N. Mack (Biological Invasions, 2013)

A direct test of nitrogen and phosphorus limitation to net primary productivity in a lowland tropical wet forest - S. Alvarez-Clare; M. C. Mack; M. Brooks (Ecology, 2013)
Experimental evidence for limitation of net primary productivity (NPP) by nitrogen (N) or phosphorus (P) in lowland tropical forests is rare, and the results from the few existing studies have been inconclusive. To directly test if N or P limit NPP in a lowland tropical wet forest in Costa Rica, we conducted a full factorial fertilization experiment (4 treatments × 6 replicates in 30 × 30 m plots). We focused on the influence of tree size and taxa on nutrient limitation, because in these forests a wide variety of tree functional traits related to nutrient acquisition and use are likely to regulate biogeochemical processes. After 2.7 years, a higher percentage of trees per plot increased basal area (BA) with P additions (66.45% ± 3.28% without P vs. 76.88% ± 3.28% with P), but there were no other community‐level responses to N or P additions on BA increase, litterfall productivity, or root growth. Phosphorus additions resulted in doubled stem growth rates in small trees (5–10 cm diameter at breast height (dbh); [ P ≤ 0.01]) but had no effect on intermediate (10–30 cm dbh) or large trees (>30 cm dbh). Phosphorus additions also increased the percentage of seedling survival from 59% to 78% ( P P = 0.03), and increased leaf number ( P = 0.02). Trees from Pentaclethra macroloba , the most abundant species, did not increase growth rates with fertilization ( P = 0.40). In contrast, the most abundant palms ( Socratea exorrhiza ) had more than two times higher stem growth rates with P additions ( P = 0.01). Our experiment reiterates that P availability is a significant driver of plant processes in these systems, but highlights the importance of considering different aspects of the plant community when making predictions concerning nutrient limitation. We postulate that in diverse, lowland tropical forests “heterogeneous nutrient limitation” occurs, not only driven by variability in nutrient responses among taxa, but also among size classes and potential functional groups. Heterogeneous responses to nutrient additions could lead to changes in forest structure or even diversity in the long term, affecting rates of NPP and thus carbon cycling.

Nutrient‐specific solubility patterns of leaf litter across 41 lowland tropical woody species - Laura A. Schreeg; Michelle C. Mack; Benjamin L. Turner (Ecology, 2013)
Leaching is a mechanism for the release of nutrients from litter or senesced leaves that can drive interactions among plants, microbes, and soil. Although leaching is well established in conceptual models of litter decomposition, potential nutrient solubility of mineral elements from recently senesced litter has seldom been quantified. Using a standardized extraction (1:50 litter‐to‐water ratio and four‐hour extraction) and recently senesced leaf litter of 41 tropical tree and liana species, we investigated how solubility varies among elements, and whether the solubility of elements could be predicted by litter traits (e.g., lignin, total element concentrations). In addition, we investigated nutrient forms (i.e., inorganic and organic) and ratios in leachate. Water‐soluble elements per unit litter mass were strongly predicted by total initial litter element concentrations for potassium (K; r 2 = 0.79), sodium (Na; r 2 = 0.51) and phosphorus (P; r 2 = 0.66), while a significant but weaker positive relationship was found for nitrogen (N; r 2 = 0.36). There was no significant relationship for carbon (C) or calcium (Ca). Element‐specific solubility varied markedly. On average 100% of total K, 35% of total P, 28% of total Na, 5% of total N, 4% of total Ca, and 3% of total C were soluble. For soluble P, 90% was inorganic orthophosphate. The high solubility of K, Na, and P as inorganic orthophosphate suggests that these nutrients can become rapidly available to litter microbes with no metabolic cost. Few common predictors of decomposition rates were correlated with element solubility, although soluble C (milligrams per gram of litter) was negatively related to lignin content ( r 2 = 0.19; P

Carbon Accumulation Patterns During Post-Fire Succession in Cajander Larch (Larix cajanderi) Forests of Siberia - Heather D. Alexander; Michelle C. Mack; Scott Goetz; Michael M. Loranty; Pieter S. A. Beck; Kamala Earl; Sergey Zimov; Sergey Davydov; Catharine C. Thompson (Ecosystems, 2012)

Environmental epigenetics: prospects for studying epigenetic mediation of exposure–response relationships - Victoria K. Cortessis; Duncan C. Thomas; A. Joan Levine; Carrie V. Breton; Thomas M. Mack; Kimberly D. Siegmund; Robert W. Haile; Peter W. Laird (Human Genetics, 2012)

Nitrogen Isotope Patterns in Alaskan Black Spruce Reflect Organic Nitrogen Sources and the Activity of Ectomycorrhizal Fungi - Jordan R. Mayor; Edward A. G. Schuur; Michelle C. Mack; Terresa N. Hollingsworth; Erland Bååth (Ecosystems, 2012)

Sinks for nitrogen inputs in terrestrial ecosystems: a meta‐analysis of 15 N tracer field studies - P. H. Templer; M. C. Mack; F. S. Chapin III; L. M. Christenson; J. E. Compton; H. D. Crook; W. S. Currie; C. J. Curtis; D. B. Dail; C. M. D'Antonio; B. A. Emmett; H. E. Epstein; et al. (Ecology, 2012)
Effects of anthropogenic nitrogen (N) deposition and the ability of terrestrial ecosystems to store carbon (C) depend in part on the amount of N retained in the system and its partitioning among plant and soil pools. We conducted a meta‐analysis of studies at 48 sites across four continents that used enriched 15 N isotope tracers in order to synthesize information about total ecosystem N retention (i.e., total ecosystem 15 N recovery in plant and soil pools) across natural systems and N partitioning among ecosystem pools. The greatest recoveries of ecosystem 15 N tracer occurred in shrublands (mean, 89.5%) and wetlands (84.8%) followed by forests (74.9%) and grasslands (51.8%). In the short term ( 15 N tracer application), total ecosystem 15 N recovery was negatively correlated with fine‐root and soil 15 N natural abundance, and organic soil C and N concentration but was positively correlated with mean annual temperature and mineral soil C:N. In the longer term (3–18 months after 15 N tracer application), total ecosystem 15 N retention was negatively correlated with foliar natural‐abundance 15 N but was positively correlated with mineral soil C and N concentration and C : N, showing that plant and soil natural‐abundance 15 N and soil C:N are good indicators of total ecosystem N retention. Foliar N concentration was not significantly related to ecosystem 15 N tracer recovery, suggesting that plant N status is not a good predictor of total ecosystem N retention. Because the largest ecosystem sinks for 15 N tracer were below ground in forests, shrublands, and grasslands, we conclude that growth enhancement and potential for increased C storage in aboveground biomass from atmospheric N deposition is likely to be modest in these ecosystems. Total ecosystem 15 N recovery decreased with N fertilization, with an apparent threshold fertilization rate of 46 kg N·ha −1 ·yr −1 above which most ecosystems showed net losses of applied 15 N tracer in response to N fertilizer addition.

Implications of climate change for Daphnia in alpine lakes: predictions from long-term dynamics, spatial distribution, and a short-term experiment - Janet M. Fischer; Mark H. Olson; Craig E. Williamson; Jennifer C. Everhart; Paula J. Hogan; Jeremy A. Mack; Kevin C. Rose; Jasmine E. Saros; Jeffery R. Stone; Rolf D. Vinebrooke (Hydrobiologia, 2011)

Associations of cardiovascular variables and HAART with cognition in middle-aged HIV-infected and uninfected women - Howard A. Crystal; Jeremy Weedon; Susan Holman; Jennifer Manly; Victor Valcour; Mardge Cohen; Kathryn Anastos; Chenglong Liu; Wendy J. Mack; Elizabeth Golub; Jason Lazar; Ann Ho; et al. (Journal of NeuroVirology, 2011)

The impacts and implications of an intensifying fire regime on Alaskan boreal forest composition and albedo - PIETER S. A. BECK; SCOTT J. GOETZ; MICHELLE C. MACK; HEATHER D. ALEXANDER; YUFANG JIN; JAMES T. RANDERSON; M. M. LORANTY (Global Change Biology, 2011)
Climate warming and drying are modifying the fire dynamics of many boreal forests, moving them towards a regime with a higher frequency of extreme fire years characterized by large burns of high severity. Plot‐scale studies indicate that increased burn severity favors the recruitment of deciduous trees in the initial years following fire. Consequently, a set of biophysical effects of burn severity on postfire boreal successional trajectories at decadal timescales have been hypothesized. Prominent among these are a greater cover of deciduous tree species in intermediately aged stands after more severe burning, with associated implications for carbon and energy balances. Here we investigate whether the current vegetation composition of interior Alaska supports this hypothesis. A chronosequence of six decades of vegetation regrowth following fire was created using a database of burn scars, an existing forest biomass map, and maps of albedo and the deciduous fraction of vegetation that we derived from Moderate Resolution Imaging Spectroradiometer (MODIS) satellite imagery. The deciduous fraction map depicted the proportion of aboveground biomass in deciduous vegetation, derived using a RandomForest algorithm trained with field data sets ( n =69, 71% variance explained). Analysis of the difference Normalized Burn Ratio, a remotely sensed index commonly used as an indicator of burn severity, indicated that burn size and ignition date can provide a proxy of burn severity for historical fires. LIDAR remote sensing and a bioclimatic model of evergreen forest distribution were used to further refine the stratification of the current landscape by burn severity. Our results show that since the 1950s, more severely burned areas in interior Alaska have produced a vegetation cohort that is characterized by greater deciduous biomass. We discuss the importance of this shift in vegetation composition due to climate‐induced changes in fire severity for carbon sequestration in forest biomass and surface reflectance (albedo), among other feedbacks to climate.

The Effects of Snow, Soil Microenvironment, and Soil Organic Matter Quality on N Availability in Three Alaskan Arctic Plant Communities - Jennie DeMarco; Michelle C. Mack; M. Syndonia Bret-Harte (Ecosystems, 2011)

Refinement of Elastic, Poroelastic, and Osmotic Tissue Properties of Intervertebral Disks to Analyze Behavior in Compression - Ian A. F. Stokes; Jeffrey P. Laible; Mack G. Gardner-Morse; John J. Costi; James C. Iatridis (Annals of Biomedical Engineering, 2011)

Short-term effects of fire on soil and plant nutrients in palmetto flatwoods - Jennifer Lynn Schafer; Michelle C. Mack (Plant and Soil, 2010)

The effect of nutrient deposition on bacterial communities in Arctic tundra soil - Barbara J. Campbell; Shawn W. Polson; Thomas E. Hanson; Michelle C. Mack; Edward A. G. Schuur (Environmental Microbiology, 2010)
Summary The microbial communities of high‐latitude ecosystems are expected to experience rapid changes over the next century due to climate warming and increased deposition of reactive nitrogen, changes that will likely affect microbial community structure and function. In moist acidic tundra (MAT) soils on the North Slope of the Brooks Range, Alaska, substantial losses of C and N were previously observed after long‐term nutrient additions. To analyse the role of microbial communities in these losses, we utilized 16S rRNA gene tag pyrosequencing coupled with community‐level physiological profiling to describe changes in MAT bacterial communities after short‐ and long‐term nutrient fertilization in four sets of paired control and fertilized MAT soil samples. Bacterial diversity was lower in long‐term fertilized plots. The Acidobacteria were one of the most abundant phyla in all soils and distinct differences were noted in the distributions of Acidobacteria subgroups between mineral and organic soil layers that were also affected by fertilization. In addition, Alpha ‐ and Gammaproteobacteria were more abundant in long‐term fertilized samples compared with control soils. The dramatic increase in sequences within the Gammaproteobacteria identified as Dyella spp. (order Xanthomonadales ) in the long‐term fertilized samples was confirmed by quantitative PCR (qPCR) in several samples. Long‐term fertilization was also correlated with shifts in the utilization of specific substrates by microbes present in the soils. The combined data indicate that long‐term fertilization resulted in a significant change in microbial community structure and function linked to changes in carbon and nitrogen availability and shifts in above‐ground plant communities.

Limitation of Finite Element Analysis of Poroelastic Behavior of Biological Tissues Undergoing Rapid Loading - Ian A. Stokes; Salman Chegini; Stephen J. Ferguson; Mack G. Gardner-Morse; James C. Iatridis; Jeffrey P. Laible (Annals of Biomedical Engineering, 2010)

Changes in fire regime break the legacy lock on successional trajectories in Alaskan boreal forest - JILL F. JOHNSTONE; TERESA N. HOLLINGSWORTH; F. STUART CHAPIN; MICHELLE C. MACK (Global Change Biology, 2010)
Predicting plant community responses to changing environmental conditions is a key element of forecasting and mitigating the effects of global change. Disturbance can play an important role in these dynamics, by initiating cycles of secondary succession and generating opportunities for communities of long‐lived organisms to reorganize in alternative configurations. This study used landscape‐scale variations in environmental conditions, stand structure, and disturbance from an extreme fire year in Alaska to examine how these factors affected successional trajectories in boreal forests dominated by black spruce. Because fire intervals in interior Alaska are typically too short to allow relay succession, the initial cohorts of seedlings that recruit after fire largely determine future canopy composition. Consequently, in a dynamically stable landscape, postfire tree seedling composition should resemble that of the prefire forest stands, with little net change in tree composition after fire. Seedling recruitment data from 90 burned stands indicated that postfire establishment of black spruce was strongly linked to environmental conditions and was highest at sites that were moist and had high densities of prefire spruce. Although deciduous broadleaf trees were absent from most prefire stands, deciduous trees recruited from seed at many sites and were most abundant at sites where the fires burned severely, consuming much of the surface organic layer. Comparison of pre‐ and postfire tree composition in the burned stands indicated that the expected trajectory of black spruce self‐replacement was typical only at moist sites that burned with low fire severity. At severely burned sites, deciduous trees dominated the postfire tree seedling community, suggesting these sites will follow alternative, deciduous‐dominated trajectories of succession. Increases in the severity of boreal fires with climate warming may catalyze shifts to an increasingly deciduous‐dominated landscape, substantially altering landscape dynamics and ecosystem services in this part of the boreal forest.

The nutrient status of epiphytes and their host trees along an elevational gradient in Costa Rica - Catherine L. Cardelús; Michelle C. Mack (Plant Ecology, 2010)

Myogenic regulatory factor response to resistance exercise volume in skeletal muscle - Micah J. Drummond; Robert K. Conlee; Gary W. Mack; Sterling Sudweeks; G. Bruce Schaalje; Allen C. Parcell (European Journal of Applied Physiology, 2010)

The influence of tree species on canopy soil nutrient status in a tropical lowland wet forest in Costa Rica - Catherine L. Cardelús; Michelle C. Mack; Carrie Woods; Jennie DeMarco; Kathleen K. Treseder (Plant and Soil, 2009)

An EST database for Liriodendron tulipifera L. floral buds: the first EST resource for functional and comparative genomics in Liriodendron - Haiying Liang; John E. Carlson; James H. Leebens-Mack; P. Kerr Wall; Lukas A. Mueller; Matyas Buzgo; Lena L. Landherr; Yi Hu; D. Scott DiLoreto; Daniel C. Ilut; Dawn Field; Steven D. Tanksley; et al. (Tree Genetics & Genomes, 2008)

Carbon allocation in boreal black spruce forests across regions varying in soil temperature and precipitation - JASON G. VOGEL; BEN P. BOND‐LAMBERTY; EDWARD A. G. SCHUUR; STITH T. GOWER; MICHELLE C. MACK; KARI E. B. O'CONNELL; DAVID W. VALENTINE; ROGER W. RUESS (Global Change Biology, 2008)
A common hypothesis for northern ecosystems is that low soil temperatures inhibit plant productivity. To address this hypothesis, we reviewed how separate components of ecosystem carbon (C) cycling varied along a soil temperature gradient for nine well‐drained, relatively productive boreal black spruce ( Picea mariana Mill. [B.S.P.]) forests in Alaska, USA, and Saskatchewan and Manitoba, Canada. Annual soil temperature [expressed as soil summed degree days (SDD)] was positively correlated with aboveground net primary productivity (ANPP), while negatively correlated with total belowground carbon flux (TBCF). The partitioning of C to ANPP at the expense of root processes represented a nearly 1 : 1 tradeoff across the soil temperature gradient, which implied that the amount of C cycling through these black spruce ecosystems was relatively insensitive to variation in SDD. Moreover, the rate at which C accumulated in the ecosystem since the last stand replacing fire was unrelated to SDD, but SDD was positively correlated to the ratio of spruce‐biomass : forest‐floor‐mass. Thus, plant partitioning of C and the distribution of ecosystem C were apparently affected by soil temperature, although across regions, precipitation co‐varied with soil temperature. These two factors likely correlated with one another because of precipitation's influence on soil heat balance, suggesting that a soil temperature–precipitation interaction could be responsible for the shifts in C allocation. Nonetheless, our results highlight that for this boreal ecosystem, ANPP and TBCF can be negatively correlated. In tropical and temperate forests, TBCF and ANPP have been reported as positively correlated, and our results may reflect the unique interactions between soil temperature, forest floor accumulation, rooting depth, and nutrient availability that characterize the black spruce forest type.

Recovery of Aboveground Plant Biomass and Productivity After Fire in Mesic and Dry Black Spruce Forests of Interior Alaska - Michelle C. Mack; Kathleen K. Treseder; Kristen L. Manies; Jennifer W. Harden; Edward A. G. Schuur; Jason G. Vogel; James T. Randerson; F. Stuart Chapin (Ecosystems, 2008)

Nutrient Addition Prompts Rapid Destabilization of Organic Matter in an Arctic Tundra Ecosystem - Nicole S. Nowinski; Susan E. Trumbore; Edward A. G. Schuur; Michelle C. Mack; Gaius R. Shaver (Ecosystems, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Plant Species Composition and Productivity following Permafrost Thaw and Thermokarst in Alaskan Tundra - Edward A. G. Schuur; Kathryn G. Crummer; Jason G. Vogel; Michelle C. Mack (Ecosystems, 2007)

Mycorrhizal responses to nitrogen fertilization in boreal ecosystems: potential consequences for soil carbon storage - KATHLEEN K. TRESEDER; KATIE M. TURNER; MICHELLE C. MACK (Global Change Biology, 2007)
Mycorrhizal fungi can contribute to soil carbon sequestration by immobilizing carbon in living fungal tissues and by producing recalcitrant compounds that remain in the soil following fungal senescence. We hypothesized that nitrogen (N) fertilization would decrease these carbon stocks, because plants should reduce investment of carbon in mycorrhizal fungi when N availability is high. We measured the abundance of two major groups of mycorrhizal fungi, arbuscular mycorrhizal (AM) and ectomycorrhizal (ECM) fungi, in the top 10 cm of soil in control and N‐fertilized plots within three Alaskan boreal ecosystems that represented different recovery stages following severe fire. Pools of mycorrhizal carbon included root‐associated AM and ECM structures; soil‐associated AM hyphae; and glomalin, a glycoprotein produced by AM fungi. Total mycorrhizal carbon pools decreased by approximately 50 g C m −2 in the youngest site under N fertilization, and this reduction was driven mostly by glomalin. Total mycorrhizal carbon did not change significantly in the other sites. Root‐associated AM structures were more abundant under N fertilization across all sites, and root‐associated ECM structures increased marginally significantly. We found no significant N effects on AM hyphae. Carbon sequestered within living mycorrhizal structures (0.051–0.21 g m −2 ) was modest compared with that of glomalin (33–203 g m −2 ). We conclude that our hypothesis was only supported in relation to glomalin stocks within one of the three study sites. As N effects on glomalin were inconsistent among sites, an understanding of the mechanisms underlying this variation would improve our ability to predict ecosystem feedbacks to global change.

Mechanical Response of a Calcified Plaque Model to Fluid Shear Force - Tiantian C. Lin; Yin Tintut; Althea Lyman; Wendy Mack; Linda L. Demer; Tzung K. Hsiai (Annals of Biomedical Engineering, 2006)

EST database for early flower development in California poppy (Eschscholzia californica Cham., Papaveraceae) tags over 6000 genes from a basal eudicot - John E. Carlson; James H. Leebens-Mack; P. Kerr Wall; Laura M. Zahn; Lukas A. Mueller; Lena L. Landherr; Yi Hu; Daniel C. Ilut; Jennifer M. Arrington; Stephanie Choirean; Annette Becker; Dawn Field; et al. (Plant Molecular Biology, 2006)

Evaluating Wolf Translocation as a Nonlethal Method to Reduce Livestock Conflicts in the Northwestern United States - ELIZABETH H. BRADLEY; DANIEL H. PLETSCHER; EDWARD E. BANGS; KYRAN E. KUNKEL; DOUGLAS W. SMITH; CURT M. MACK; THOMAS J. MEIER; JOSEPH A. FONTAINE; CARTER C. NIEMEYER; MICHAEL D. JIMENEZ (Conservation Biology, 2005)
Successful nonlethal management of livestock predation is important for conserving rare or endangered carnivores. In the northwestern United States, wolves ( Canis lupus ) have been translocated away from livestock to mitigate conflicts while promoting wolf restoration. We assessed predation on livestock, pack establishment, survival, and homing behavior of 88 translocated wolves with radiotelemetry to determine the effectiveness of translocation in our region and consider how it may be improved. More than one‐quarter of translocated wolves preyed on livestock after release. Most translocated wolves (67%) never established or joined a pack, although eight new packs resulted from translocations. Translocated wolves had lower annual survival (0.60) than other radio‐collared wolves (0.73), with government removal the primary source of mortality. In northwestern Montana, where most wolves have settled in human‐populated areas with livestock, survival of translocated wolves was lowest (0.41) and more wolves proportionally failed to establish packs (83%) after release. Annual survival of translocated wolves was highest in central Idaho (0.71) and more wolves proportionally established packs (44%) there than in the other two recovery areas. Translocated wolves showed a strong homing tendency; most of those that failed to home still showed directional movement toward capture sites. Wolves that successfully returned to capture sites were more likely to be adults, hard (immediately) rather than soft (temporarily held in enclosure) released, and translocated shorter distances than other wolves that did not return home. Success of translocations varied and was most affected by the area in which wolves were released. We suggest managers translocating wolves or other large carnivores consider soft releasing individuals (in family groups, if social) when feasible because this may decrease homing behavior and increase release‐site fidelity.

Postfire Soil N Cycling in Northern Conifer Forests Affected by Severe, Stand-Replacing Wildfires - Erica A. H. Smithwick; Monica G. Turner; Michelle C. Mack; F. Stuart Chapin (Ecosystems, 2005)

The Effects of Exotic Grasses on Litter Decomposition in a Hawaiian Woodland: The Importance of Indirect Effects - Michelle C. Mack; Carla M. D’Antonio (Ecosystems, 2003)

Morphological and genetic evidence for vicariance and refugium in Atlantic and Gulf of Mexico populations of the hermit crab Pagurus longicarpus - Young A.; Torres C.; Mack J.; Cunningham C. (Marine Biology, 2002)

Cerebral localization and regulation of the cell volume-sensitive serum- and glucocorticoid-dependent kinase SGK1 - S. Wärntges; B. Friedrich; G. Henke; C. Duranton; P. Lang; S. Waldegger; R. Meyermann; D. Kuhl; E. Speckmann; N. Obermüller; R. Witzgall; A. Mack; et al. (Pflügers Archiv - European Journal of Physiology, 2002)

Reliability of leg muscle electromyography in vertical jumping - Peter C. Goodwin; Kobus Koorts; Richard Mack; Shunfu Mai; Matthew C. Morrissey; David M. Hooper (European Journal of Applied Physiology, 1999)